Moran’s I Index and KKN-Based LISA: Spatial Analysis of Toddler Stunting in Indonesia 2024 (Jurnal Bina Praja, 2025)
Stunting in toddlers is a significant nutritional issue that may negatively impact the quality of Indonesia’s future human resources. This study aims to analyze the spatial patterns of stunting prevalence in toddlers in Indonesia as a basis for developing region-based policy interventions. A quantitative approach was used through spatial autocorrelation analysis using Moran’s I Index and Local Indicators of Spatial Autocorrelation (LISA), which is based on the K-Nearest Neighbors (KNN) method. Stunting prevalence data were obtained from 514 districts/cities in Indonesia and analyzed to detect clustering patterns in high-risk areas. The results showed a Moran’s I of 0.315 (P-value
Keywords: Spatial Analysis; Moran’s I Index; Policy Intervention; LISA; Stunting